Natural and artificial radioactivity levels and external radiation dose levels of sand samples collected from Lara Beach, Antalya, Türkiye - Taskopru, Caner; Ozden, Selin; Gunay, Osman; Pehlivanoglu, Serpil Akozcan; Sac, Murat; Ichedef, Mutlu (SPRINGER, 2024)
This paper represents beach sand samples' natural and anthropogenic radionuclide concentrations and calculated external radiation dose levels. The radioactivity concentrations of eU (226Ra), eTh (232Th), 40K, and 137Cs were measured by gamma spectrometry using an HPGe detector. The activity concentrations ranged from 1.8 to 27.7 Bq kg-1, 5.7 to 19.5 Bq kg-1, 49.8 to 457.9 Bq kg-1, and 0.2 to 5.6 Bq kg-1 for eU, eTh, 40K and 137Cs, respectively. The radiological hazard parameters were compared to the international reference values. The results show that all data obtained are below the world average, meaning the radiation hazard is insignificant.
Keywords: Environmental radioactivity; Dose estimations; Beach sand; Gamma ray spectrometry; HPGe detector; RADIOLOGICAL HAZARD INDEXES; PARTICLE-SIZE FRACTIONS; ANTHROPOGENIC RADIONUCLIDES; COASTAL SEDIMENTS; CS-137; RADIOCESIUM; TAMILNADU; EVOLUTION; REGION; ISLAND; Chemistry; Nuclear Science & Technology